Emerging role of leptin in rheumatoid arthritis. (24th July 2014) - Tian, G; Liang, J-N; Wang, Z-Y; Zhou, D
Summary: Numerous studies have suggested the importance of leptin against autoimmune diseases such as systemic lupus erythematosus (SLE), multiple sclerosis (MS) and psoriasis. To summarize our current understanding of the role of leptin in inflammatory responses and rheumatoid arthritis (RA), a systematic review was conducted to assess the discrepancy of leptin in RA and its effect on immunity according to different studies. Recently, emerging data have indicated that leptin is involved in the pathological function of RA, which is common in autoimmune disorders. This review discusses the possible consequences of leptin levels in RA. Blocking the key signal pathways of leptin and inhibiting the leptin activity-like leptin antagonist may be a promising way for potential therapeutic treatment of RA at risk of detrimental effects. However, leptin was increased in patients with RA and may also regulate joint damage. Thus, more understanding of the mechanism of leptin in RA would be advantageous in the future.